Street bikes - Pupeza, Lori Kinstad (Minneapolis, MN : Abdo & Daughters, 1999)
Discusses the history, riding, and racing of street bikes, including such aspects as the engine, other parts, gear, and safety tips.
Includes index.
Keywords: Motorcycles -- Juvenile literature; Motorcycles